Postoperative dry eye following femtosecond laser-assisted cataract surgery: insights and preventive strategies - Lin, Bin; Li, Dong-kan; Zhang, Ling; Chen, Long-long; Gao, Ying-ying (Frontiers in Medicine, 2024)
Postoperative dry eye is a common complication following femtosecond laser-assisted cataract surgery, and the patient interface (PI) used during the procedure may play a significant role in its occurrence. This study, utilizing a meticulous scientific search strategy, identified seven relevant articles through literature search engines. Most of these studies employed contact-type PI during surgeries, while one researcher used a non-contact PI. All studies assessed dry eye symptoms at various postoperative periods using metrics such as the Ocular Surface Disease Index (OSDI), tear Break-Up Time (BUT), Schirmer I test (SIt), and so on. However, the findings were inconsistent. On this basis, this comprehensive review delves into the potential impact of different patient interfaces on corneal nerve damage and conjunctival goblet cell injury, possibly contributing to an increased risk of postoperative dry eye. The review also explores various preventive and solution strategies, including improving PI design, reducing surgical time, and utilizing tear protective agents. The findings highlight the importance of optimizing the PI to minimize the risk of postoperative dry eye in femtosecond laser-assisted cataract surgery.